Impact of regional diversity on production potential: An example of Russia - Maria Belyaeva; Heinrich Hockmann (Studies in Agricultural Economics, 2015)
Russia is often considered the most prominent country to become a leader on the world grain market. However, several issues slow down Russia's agricultural progress, for example: a lack of infrastructure and investments, unequal regional development and inefficient use of production technologies. This study therefore examines the grain production potential of Russian regions by employing a modified approach to stochastic frontier analysis that allows us to include not only production technologies, but also indicators of the country's heterogeneity and diversity among regions. The results obtained indicate that climate conditions in combination with the level of human and institutional development, and infrastructure have significant effects on the production structure of regions and therefore should not be neglected while assessing regional policies and production potential.
Keywords: 330; technical efficiency; stochastic frontier analysis; heterogeneity; production potential